The lost symbol (Robert Langdon novels, 3, 1, 2009)
The discovery of a mysterious object in the U.S. Capitol building and a subsequent kidnapping lead Harvard symbologist Robert Langdon into a web of mysterious codes, secret locations, and hidden knowledge